Von Willebrand factor as a thrombotic and inflammatory mediator in critical illness. Issue Volume 60:Issue S3(2020) (1st June 2020) - Plautz, William E.; Matthay, Zachary A.; Rollins‐Raval, Marian A.; Raval, Jay S.; Kornblith, Lucy Z.; Neal, Matthew D.
Abstract : The endothelial exocytosis of high‐molecular‐weight multimeric von Willebrand factor (vWF) may occur in critical illness states, including trauma and sepsis, leading to the sustained elevation and altered composition of plasma vWF. These critical illnesses involve the common process of sympathoadrenal activation and loss of the endothelial glycocalyx. As a prothrombotic and proinflammatory molecule that interacts with the endothelium, the alterations exhibited by vWF in critical illness have been implicated in the development and damaging effects of downstream pathologies, such as disseminated intravascular coagulation and systemic inflammatory response syndrome. Given the role of vWF in these pathologies, there has been a recent push to further understand how the molecule may be involved in the pathophysiology of related diseases, such as trauma‐induced coagulopathy and acute renal injury, which are also known to develop secondarily to critical illness states. Elucidation of the role of vWF across the broader spectrum of generalized pathologies may provide a basis for the development of novel preventative and restorative measures, while also bolstering the scaffold of more widely used treatments, such as the administration of plasma‐containing blood products.